Some Comments About The Real Members Of The Academy Of Sciences Of The Republic Of Uzbekistan – Academicians - Ismailov Alisher (Zien Journals, 2021)
This article discusses important aspects of the author’s academics of the Academy of Sciences. It includes elections for full membership of the Academy of Sciences, the number of academics, the list of academic women, the age indicators of academicians (minimum age, average age, oldest age), ethnic composition, place of birth, number and rating of academicians in the field of science are covered on the basis of archival sources. Through this aspect of the matter, it serves as the main material about the academics of the Academy of Sciences
Keywords: Academic; once every two years; at least once every three years; election